ETHICAL ISSUES IN PLASTIC SURGERY: MODERN ACHIEVEMENTS AND PROSPECTS - Miraskad Isomov (Innovate Conferences, 2025)
Plastic surgery is one of the most dynamically developing areas of modern medicine, associated not only with medical, but also with ethical and legal aspects. The growing popularity of aesthetic surgery raises many questions related to patients' rights, the professional ethics of doctors and the regulation of this field. The article examines major ethical dilemmas, including the balance between medical necessity and aesthetic needs, informed consent, and the social consequences of plastic surgery. Legal issues such as the regulation of the professional activities of surgeons, liability for possible complications and the role of medical standards are also analyzed.
Keywords: plastic surgery, medical ethics, legal aspects, aesthetic medicine, informed consent, patient rights, professional responsibility.